Paleozoic tectonic evolution of the eastern Central Asian Orogenic Belt in NE China - Yong-fei Ma; Yong-jiang Liu; A.Yu. Peskov; Yan Wang; Wei-min Song; Yu-jin Zhang; Cheng Qian; Tong-jun Liu (China Geology, 2022)
The eastern Central Asian Orogenic Belt (CAOB) in NE China is a key area for investigating continental growth. However, the complexity of its Paleozoic geological history has meant that the tectonic development of this belt is not fully understood. NE China is composed of the Erguna and Jiamusi blocks in the northern and eastern parts and the Xing’an and Songliao-Xilinhot accretionary terranes in the central and southern parts. The Erguna and Jiamusi blocks have Precambrian basements with Siberia and Gondwana affinities, respectively. In contrast, the Xing ’an and Songliao-Xilinhot accretionary terranes were formed via subduction and collision processes. These blocks and terranes were separated by the Xinlin-Xiguitu, Heilongjiang, Nenjiang, and Solonker oceans from north to south, and these oceans closed during the Cambrian (ca. 500 Ma), Late Silurian (ca. 420 Ma), early Late Carboniferous (ca. 320 Ma), and Late Permian to Middle Triassic (260 –240 Ma), respectively, forming the Xinlin-Xiguitu, Mudanjiang-Yilan, Hegenshan-Heihe, Solonker-Linxi, and Changchun-Yanji suture zones. Two oceanic tectonic cycles took place in the eastern Paleo-Asian Ocean (PAO), namely, the Early Paleozoic cycle involving the Xinlin-Xiguitu and Heilongjiang oceans and the late Paleozoic cycle involving the Nenjiang-Solonker oceans. The Paleozoic tectonic pattern of the eastern CAOB generally shows structural features that trend east-west. The timing of accretion and collision events of the eastern CAOB during the Paleozoic youngs progressively from north to south. The branch ocean basins of the eastern PAO closed from west to east in a scissor-like manner. A bi-directional subduction regime dominated during the narrowing and closure process of the eastern PAO, which led to “soft collision” of tectonic units on each side, forming huge accretionary orogenic belts in central Asia.©2022 China Geology Editorial Office.